Monitoração ambiental no Setor de Tecnologias da Informação das Regiões Sul e Sudeste do Brasil: um estudo sobre fontes de informação e aspectos ambientais - Jaime Sadao Yamassaki Bastos (2005)
This work investigates how Brazilian managers deal with externalinformation. The study carries out a survey with managers of informationtechnology companies in south and southeast regions of Brazil. It analyses the perceived change level and the importance attributed by 92 managers to aspects of their companies external environments. It also considers the frequency of use and their perceptions about relevance and reliability of external information sources. The results reveal the high dynamism and importance of aspects related to technology and clients. Regarding the information sources, external sources were considered more relevant and reliable, being more frequently used by managers. The findings are compared with similar previous studies and suggestions to new researches are presented, with emphasis on the development of a wide research agenda about this subject in Brazil.